METEOROLOGICAL DATA AT MIZUHO STATION, ANTARCTICA IN 1985 - KIKUCHI, Tokio; SHIMAMOTO, Takashi; OKUHIRA, Fumio; AGETA, Yutaka (National Institute of Polar Research, 1986)
P(論文) departmental bulletin paper